2007
DOI: 10.1590/s1679-62252007000300015
|View full text |Cite
|
Sign up to set email alerts
|

The fish fauna of Brokopondo Reservoir, Suriname, during 40 years of impoundment

Abstract: We investigated long-term changes in the fish fauna of Brokopondo Reservoir, Suriname, the first large reservoir (1560 km 2 ) that was created in tropical rainforest. Before closure of the dam in 1964, the fish fauna of Suriname River had 172 species, high diversity and high evenness. The riverine fauna was dominated by small-sized species, but no single species was dominant in numbers. Large catfishes were dominant in biomass. Species were evenly distributed over riverine habitats: rapids, tributaries and mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 27 publications
0
30
1
6
Order By: Relevance
“…Como investigado em outros reservatórios (aGOstinhO et al, 1997;aBelha et al, 2001;CasseMiRO et al, 2002;hahn et al, 2002;dias et al, 2005;MOl et al, 2007;BenneMann et al, 2011;delaRiVa et al, 2013) os recursos alimentares tendem a sofrer modificações com o decorrer dos anos após o represamento. hahn et al (1997) analisaram o reservatório de Segredo recém construído e observaram que após o primeiro ano de formação, os principais recursos alimentares consumidos já não eram mais em sua maioria alóctones.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Como investigado em outros reservatórios (aGOstinhO et al, 1997;aBelha et al, 2001;CasseMiRO et al, 2002;hahn et al, 2002;dias et al, 2005;MOl et al, 2007;BenneMann et al, 2011;delaRiVa et al, 2013) os recursos alimentares tendem a sofrer modificações com o decorrer dos anos após o represamento. hahn et al (1997) analisaram o reservatório de Segredo recém construído e observaram que após o primeiro ano de formação, os principais recursos alimentares consumidos já não eram mais em sua maioria alóctones.…”
Section: Discussionunclassified
“…O material lenhoso também favorece a colonização de uma fauna associada e diversificada, especialmente de insetos, aumentando a diversidade de peixes nestes habitats, uma vez que são fontes potenciais de alimentos (OliVeiRa & BenneMann, 2005), o que justifica o fato desta zona apresentar a maior quantidade de guildas. aGOstinhO & JuliO JR (1999) e MOl et al (2007) relataram que em reservatórios antigos e rasos os alimentos encontrados em maior abundância são insetos e detritos, corroborando assim com os resultados obtidos no presente estudo visto que, das 13 espécies estudadas, 12 foram capturadas nesta zona e a riqueza de espécies de detritívoros foi maior quando comparada às outras zonas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A short, fine sediment-based food chain (sediment-Hemiodus-Serrasalmus) (Mol et al 2007). Mol et al (2007) reported stunting in the piranha population of the Brokopondo Reservoir. This means that small piranhas may be relatively old.…”
Section: Fishmentioning
confidence: 99%